FRI0350 Lupus low disease activity state (LLDAS-50) is a significant predictor for damage accrual and mortality: a norwegian cohort analysis. (12th June 2018) - Sharma, C.; Raymond, W.; Eilertsen, G.; NOSSENT, J.
Abstract : Background: Disease activity in patients with Systemic Lupus Erythematosus (SLE) is an important contributor to organ damage and premature mortality. Current indices to capture disease activity are not well suited to reflect their contribution to long term outcome. Lupus Low Disease Activity State (LLDAS) has been developed as an alternative measure of long term disease activity. Objectives: To determine whether 50% of time spent in Lupus Low Disease Activity State (LLDAS-50) impacts on mortality and damage accrual in SLE Methods: A retrospective analysis of prospectively collected data was conducted on 3650 clinic visits by 207 patients in the Tromsø Lupus Cohort. Lupus Low Disease Activity State −50 (LLDAS50) score was defined as at least 50% of follow-up time with SLE Disease Activity Index (SLEDAI) ≤4, no new disease activity, prednisone ≤7.5  mg/day and no escalation of maintenance immunosuppressant therapy. Cox regression analysis was used to evaluate the impact of LLDAS50 in terms of mortality and damage development (either new or severe) by Systemic Lupus Erythematosus Clinical Criteria (SLICC)/American College of Rheumatology (ACR) Damage Index (SDI). New damage was defined as a rise in SDI by 1 from baseline whereas severe damage was defined as a rise of 3 points or more from baseline. Results: The median age at diagnosis of the cohort was 34 years with the majority (84%) being female. The median follow-up time was 125 months. A total of 69 patients (33.5%) spent at least half of their follow up time in LDAS, thus achieving LLDAS50. After correction for age and gender, LLDAS-50 was associated with a significant reduction in risk of having any new damage (OR 0.65; 95% CI 0.44–0.96, p<0.01), severe damage (OR 0.46; 95% CI 0.25–0.83, p<0.01), and also a reduction in mortality risk (OR 0.42; 95% CI 0.21–0.82, p<0.01). These values were also tested for those patients who spent 30% or more time in LDAS, and were also found to be significant for death (OR 0.46, 95% CI. 26-0.83, p<0.05) but not for new damage (OR 0.92, 95% CI 0.62–1.35, p=0.67) or severe damage (OR 0.71, 95% CI 0.42–1.19, p=0.19). Conclusions: The significant reduction in the risk of long term damage and mortality supports the use of LLDAS50 as a therapeutic goal. Disclosure of Interest: None declared